An investigation into the effects of the shifting centroid and shear centre in notched steel beams undergoing elastic lateral torsional buckling - Aldera, Gianluca (Department of Civil Engineering, 2023)
Notched steel sections have been investigated since the late 1970s and early 1980s. Notched sections are interesting since, for a doubly symmetric member, part of the section is singly or monosymmetric – specifically the notched region – while the un-notched portion may be a standard section. Since the notched region is monosymmetric the centroid and shear centre in this region are at different vertical heights. The design for Lateral Torsional Buckling (LTB) in standard prismatic sections accounts for the monosymmetry through the monosymmetry factor which accounts for the additional twisting moment. However, this is not used in the analysis of notched regions for beams that are laterally unrestrained. These regions are stiffened against local buckling failure using horizontal and vertical stiffeners. The horizontal stiffeners make the notched part appear as an H or I shaped section. Using downstands on the horizontal stiffener the centroid and shear centre in the notched region can be shifted relative to each other – and in some cases - to be at the same vertical height (which is the case for the un-notched sections). This study looks into how the addition of stiffeners in the notched region of a doubly symmetric beam affects the centroid and shear centre location for top notched steel sections undergoing elastic lateral torsional buckling, and how the shifting shear centre relates to the critical elastic moment. A parametric study using a Finite Element Model (FEM) using the Finite Element Analysis (FEA) software Abaqus was used to conduct the study. This research tested 5 steel sections (203x133x25, 305x102x25, 533x210x82, 203x203x46 and 305x305x97) with four different spans (1m,3m and 5m,6m) and two loading cases (unit point load 600mm from notched end and a unit point load at mid span) to investigate the influence of the shifting centroid and shear centre. Initially, 13 stiffening techniques were tested on the 203x133x25 section to identify the five best performing techniques. These were improved, then tested on all five sections. Downstands were applied to the horizontal stiffener, their purpose being to shift the shear centre upwards and past the centroid. With each increase in downstand height the shear centre would approach the centroid and eventually move past it. The critical elastic moment increased with the addition of downstands in almost all cases. The increase was independent of changes to the spans or loading configurations. Changes in the trend were evident as changes in gradient or changes in curve type around the centroid shear centre coincidence point. This shows a link between the centroid, shear centre and the critical elastic moment. Further research should be undertaken on the FHEN and FHHVNTS techniques by applying them to many steel sections to see if the results are consistent for a general case. Care should be taken to allow for downstands far beyond the centroid shear centre coincidence point to see if all sections tend to the same result. Future studies should focus on isolating the changes due to the shear centre centroid movement versus the change in overall geometric properties.